Chapter Solution-Processed Graphene-Based Transparent Conductive Electrodes as Ideal ITO Alternatives for Organic Solar Cells - Stylianakis, Minas M. (InTechOpen, 2017)
The isolation of free-standing graphene in 2004 was the spark for a new scientific revolution in the field of optoelectronics. Due to its extraordinary optoelectronic and mechanical properties, graphene is the next wonder material that could act as an ideal low-cost alternative material for the effective replacement of the expensive conventional materials used in organic optoelectronic applications. Indeed, the enhanced electrical conductivity of graphene combined with its high transparency in visible and near-infrared spectra, enabled graphene to be an ideal low-cost indium tin oxide (ITO) alternative in organic solar cells (OSCs). The prospects and future research trend in graphene-based TCE are also discussed. On the other hand, solution-processed graphene combines the unique optoelectrical properties of graphene with large area deposition and flexible substrates making it compatible with printing and coating technologies, such as roll-to-roll, inkjet, gravure, and flexographic printing manufacturing methods. This chapter provides an overview of the most recent research progress in the application of solution-processed graphene-based films as transparent conductive electrodes (TCEs) in OSCs. (a) Chemically converted graphene (CCG), (b) thermally and photochemically reduced graphene oxide, (c) composite reduced graphene oxide-carbon nanotubes, and (d) reduced graphene oxide mesh films have demonstrated their applicability in OSCs as transparent, conductive electrodes.